2020
DOI: 10.1016/j.plefa.2020.102094
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of dietary polyunsaturated fats between humans and rodents: A review of allometric scaling models

Abstract: The purpose of this research was to explore various allometric scaling models for dietary nutrients to improve translational validity between preclinical experimental rodent models and humans, focusing on polyunsaturated fats. Currently, there is no authoritative document that provides standardized guidelines for which dietary designs can be based on to improve translational fidelity between species. This paper reviews the challenges of using a rodent model, the major allometric scaling models, the use of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The modified high DHA diet contained approximately 5.88 g DHA/kg, or 1.4% of kcal from DHA. This corresponds to a person taking approximately 3.11 g/day based on a 2000 kcal diet [ 25 ]. This dose was chosen based on the evidence that the anti–inflammatory and cardioprotective effects attributed to omega-3 fatty acids are within the range of 1-5 g omega-3 fatty acids [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The modified high DHA diet contained approximately 5.88 g DHA/kg, or 1.4% of kcal from DHA. This corresponds to a person taking approximately 3.11 g/day based on a 2000 kcal diet [ 25 ]. This dose was chosen based on the evidence that the anti–inflammatory and cardioprotective effects attributed to omega-3 fatty acids are within the range of 1-5 g omega-3 fatty acids [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Paper between 4 and 20 g of RS per day based on the energy needs conversion factor for mice to humans and average feed consumption for mice consuming between 2-10% RPS. 65 Alphadiversity was significantly decreased in mice fed the 10% VF diet, but the 5% VF group was only significantly different from the basal group in the Shannon diversity plot and the 2% group was not different from the basal diet in all three alpha diversity plots. We and others have also shown that feeding RS can decrease alpha diversity in rodents.…”
Section: Food and Functionmentioning
confidence: 85%
“…A high-cholesterol laboratory diet in rodents provides 1%–2% of daily calories as cholesterol, a level one to two thousand times greater than the average human cholesterol intake as a percentage of daily calories in an animal with a lower baseline fat intake. In addition, due to higher metabolic rates, rodents have a higher tissue requirement for omega-3 fatty acids, impairing translational validity between species ( Whelan and Whelan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%